A conceptual architecture for semantic web services development and deployment. (19th December 2005) - Pahl, Claus
Several extensions of the Web Services Framework (WSF) have been proposed. The combination with semantic web technologies introduces a notion of semantics, which can enhance scalability through automation. Service composition to processes is an equally important issue. Ontology technology, the core of the semantic web, can be the central building block of an extension endeavour. We present a conceptual architecture for ontology-based web service development and deployment. The development of service-based software systems within the WSF is gaining increasing importance. We show how ontologies can integrate models, languages, infrastructure, and activities within this architecture to support reuse and composition of semantic web services.